How Do Foreign Directors Affect Assurance Practices in Sustainability Reporting? - Pebriani, Reny Aziatul; Syafitri, Lili (Universitas Indo Global Mandiri, 2024)
Sustainability reports are an important element in modern corporate governance practices, especially in ensuringtransparency and accountability to stakeholders. The use of assurance in sustainability reports is often associated withthe quality of reporting. This study examines the role of foreign directors in driving companies' decisions to use assurancein their sustainability reports. This study uses a quantitative approach with data from companies listed on the IndonesiaStock Exchange. Using empirical data from multinational corporations, this study integrates corporate governancetheory and cross-cultural perspectives to explore the influence of international experiences and cultural differences offoreign directors on transparency and accountability of sustainability reporting. The results of the study show that theexistence of foreign directors is positively related to the company's decision to use assurance in its sustainability report.This shows the importance of the global perspective brought by foreign directors in sustainability reporting practices.Foreign directors tend to bring experience and best practices from their home countries, which often have strictersustainability regulations. In addition, the study found that the impact of foreign directors is more significant in theenvironment of companies operating in countries with weak governance or low levels of sustainability compliance. Thisresearch makes an important contribution to the sustainability reporting literature, by highlighting the role of diversityin the board of directors in encouraging better reporting practices. This article also has practical implications forcompanies looking to improve the credibility of their sustainability reports in the eyes of global stakeholders. Keywords: Foreign Director, Assurance, Sustainability Report, Corporate Governance.